Global Interactome Mapping of Mitochondrial Intermembrane Space Proteases Identifies a Novel Function for HTRA2. Issue 24 (16th December 2019) - Botham, Aaron; Coyaud, Etienne; Nirmalanandhan, Victor Sanjit; Gronda, Marcela; Hurren, Rose; Maclean, Neil; St‐Germain, Jonathan; Mirali, Sara; Laurent, Estelle; Raught, Brian; Schimmer, Aaron
Abstract: A number of unique proteases localize to specific sub‐compartments of the mitochondria, but the functions of these enzymes are poorly defined. Here, in vivo proximity‐dependent biotinylation (BioID) is used to map the interactomes of seven proteases localized to the mitochondrial intermembrane space (IMS). In total, 802 high confidence proximity interactions with 342 unique proteins are identified. While all seven proteases co‐localized with the IMS markers OPA1 and CLPB, 230 of the interacting partners are unique to just one or two protease bait proteins, highlighting the ability of BioID to differentiate unique interactomes within the confined space of the IMS. Notably, high‐temperature requirement peptidase 2 (HTRA2) interacts with eight of 13 components of the mitochondrial intermembrane space bridging (MIB) complex, a multiprotein assembly essential for the maintenance of mitochondrial cristae structure. Knockdown of HTRA2 disrupts cristae in HEK 293 and OCI‐AML2 cells, and leads to increased intracellular levels of the MIB subunit IMMT. Using a cell‐free assay it is demonstrated that HTRA2 can degrade recombinant IMMT but not two other core MIB complex subunits, SAMM50 and CHCHD3. The IMS protease interactome thus represents a rich dataset that can be mined to uncover novel IMS protease biology.